Technical viability of using eggshells powder in concrete mix / Fazeera Ujin - Ujin, Fazeera (2018)
The evident rise of cement demand in some developing countries as well as the upsurge concerns on environmental issues regarding to cement resources and solid waste dumping has call for the usage of alternative cement materials from different sustainable resources that can deliver less negative impacts to the environment. The usage of Eggshells Powder (ESP) is commendable as an alternative for cement due to its similar chemical composition with the Ordinary Portland Cement (OPC) where both materials are principally composed of Calcium Carbonate (CaO). The Eggshells Powder (ESP) used in this study is a food waste from a bakery shop whereby the utilisation of food waste as a partial replacement material in concrete mix corresponds with the significant efforts on addressing environmental issues on solid waste dumping caused by rapid urbanisation in most developing countries. In this sense, environmental issues can be potentially resolved by recycling the food waste to produce applicable construction components. Therefore, this research deals with the viability and suitability of food waste material in concrete mixes.